Exploring age and gender variations in root canal morphology of maxillary premolars in Saudi sub population: a cross-sectional CBCT study - Mohmed Isaqali Karobari; Azhar Iqbal; Rumesa Batul; Abdul Habeeb Adil; Jamaluddin Syed; Hmoud Ali Algarni; Meshal Aber Alonazi; Tahir Yusuf Noorani (BMC, 2024)
Abstract Background In complex teeth like maxillary premolars, endodontic treatment success depends on a complete comprehension of root canal anatomy. The research on mandibular premolars' root canal anatomy has been extensive and well-documented in existing literature. However, there appears to be a notable gap in available data concerning the root canal anatomy of maxillary premolars. This study aimed to explore the root canal morphology of maxillary premolars using cone-beam computed tomography (CBCT) imaging, considering age and gender variations. Methods From 500 patient CBCT scans, 787 maxillary premolar teeth were evaluated. The sample was divided by gender and age (10-20, 21-30, 31-40, 41-50, 51-60, and 61 years and older). Ahmed et al. classification system was used to record root canal morphology. Results The most frequent classifications for right maxillary 1st premolars were 2MPM1 B1 L1 (39.03%) and 1MPM1 (2.81%), while the most frequent classifications for right maxillary 2nd premolars were 2MPM1 B1 L1 (39.08%) and 1MPM1 (17.85%). Most of the premolars typically had two roots (left maxillary first premolars: 81.5%, left maxillary second premolars: 82.7%, right maxillary first premolars: 74.4%, right maxillary second premolars: 75.7%). Left and right maxillary 1st premolars for classes 1MPM1 and 1MPM1-2−1 showed significant gender differences. For classifications 1MPM1 and 1MPM1-2−1, age-related changes were seen in the left and right maxillary first premolars. Conclusion This study provides novel insights into the root canal anatomy of maxillary premolars within the Saudi population, addressing a notable gap in the literature specific to this demographic. Through CBCT imaging and analysis of large sample sizes, the complex and diverse nature of root canal morphology in these teeth among Saudi individuals is elucidated. The findings underscore the importance of CBCT imaging in precise treatment planning and decision-making tailored to the Saudi population. Consideration of age and gender-related variations further enhances understanding and aids in personalized endodontic interventions within this demographic.